Territorial status of the Western Belarusian lands in the Soviet-Polish relations during the World War II and the Great Patriotic War - Velikiy, Anatoly F. (Journal of the Belarusian State University. International Relations, 2018)
The  article  is  devoted  to  the  analysis  of  problems  in  the  Soviet-Polish  bilateral  relations  during  World  War II  and  the  Great  Patriotic  War  (1939 –1945).  International  relations  during  that  period  present  the  object  of  the  study,  the  Soviet-Polish bilateral  relations  during  that  period  is  the  study  subject. The purpose of  research  is  to  characterize  the  role  and  place  of the  Western  Belarusian  lands  united  with  Belarus  in  autumn  1939  in  the mutual  relations  between  the  USSR  authorities and  the  Polish  government  in  exile,  left powers of the Polish national liberation movement (Union of Polish Patriots, Polish Committee  of  National  Liberation,  Krajova  Rada Narodova).  The main  task  of  the  USSR government  at  that time  was  to preserve  territories  which  became  part  of  the  territory  of  the  Soviet  Union  in  autumn  1939,  including  the  territory  of  Western Belarus.  The international  legal  recognition  of  unification  of  Western  Belarus  and  the  BSSR  took  place  only  in  1945,  when Belarus  became  the  member  of  the  United  Nation  Organization.
Keywords: boundary; Great Patriotic War; Soviet-Polish border; Poland; Polish government in exile; Soviet Union; UN; unite; Western Belarus; World War II